Patterns of muscle activation underlying multi-joint movements with reversal in judo - Lestienne, K. J. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
Introduction This pilot study was developed to explore the multi-muscle control based on the notion of actionproducing frames of reference for motor control. These notions are inherent in the theoretical framework of the Feldman`s ? ?model and the referent body configuration. The basic idea suggests that each muscle is activated depending on the difference between the actual and the threshold length, ?. The activation threshold ? may be defined not only for a single muscle but also for a group of muscles spanning a joint -the threshold joint angle- and even for all skeletal muscles of the body. In this latter case, we were talking about the configuration of the body described by a set of threshold values of all joint angles of the body. This is a particular configuration (R) of the body at which all skeletal muscles reach their activation thresholds simultaneously: all working muscles would simultaneously reach their minimal activity. In movement with reversal in direction the R configuration and the actual body configuration (Q) may transiently match each other (Q=R). In this pilot work the prediction on the existence of a global EMG minima in the activity of multiple skeletal muscles has been tested experimentally by analysing a movement with reversal requiring extreme changes in head-trunk-leg orientation as well as balance control. Material and Method EMG and kinematics patterns have been recorded on five Black Belt Judo experts. Based on the results on national tournaments, two distinct levels of judo training has been defined: high (Eh) and middle (Em). Subjects performed a reversal attack -Uchi-Komi in O-Soto-Gari-. The same task was repeated ten times and performed in the sagittal plane. EMG recordings were taken from the left (L) and right (R) arm and leg muscles using surface pre-amplifier electrodes (Motion Lab Systems): deltoidus [DL, DR], biceps brachii [BBL, BBR], triceps brachii [TBL, TBR], quadriceps femoris [QFL, QFR], biceps femoris [BFL, BFR]. EMG signals of each muscle were band-pass filtered (20 to 2000 Hz at -3 dB) sampled at a rate of 50 kHz. The planar body kinematics data were recorded by a 3D vision motion analyser (sampling frequency 25 Hz). Results The results clearly reveal that : 1) Eh group shows a more flexed posture comparatively to the Em group despite the variety of the EMG patterns and the functional diversity of leg and arm muscles , Eh group shows a global EMG minima before the reversal phase indicated by the dotted line whereas this minima occurs after the reversal phase in the Em group.